PENGARUH CITRA MEREK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK TAS BRANDED TIRUAN PADA WANITA KARIR DI JAKARTA - Erlita Prasetyaningsih; Rina Astini (Universitas Mercu Buana, 2016)
Women aren’t spared from the development of fashion and trends that occur around them. Especially thefashiontrends,theproducerscreateproductsthatcanattractcareerwomen.Thisisbecausecareerwomenhave more ability to buy goodsthat canimprove herclass.This researchaims todeterminethe influenceofbrand image and lifestyle on purchasing decisions imitation branded bags on the career woman in Jakarta.The population in this research is the career woman who likes to use a branded bag. Samples used were asmany as 100 people. The sampling technique using is purposive sampling. To answer the problemformulation,purposeandhypothesisofthisstudy,theanalysisemployedisIBMSPSSVer.21.0.Basedontheanalysis IBMSPSS Ver. 21.0 can be concluded that brand image have positive and significant impact onpurchasingdecisions.Thenlifestylehaspositiveandsignificantimpactonpurchasingdecisions.